Curing the Toxicity of Multi-Walled Carbon Nanotubes through Native Small-molecule Drugs - Wei Qi (Nature Portfolio, 2017)
Abstract With the development and application of nanotechnology, large amounts of nanoparticles will be potentially released to the environment and possibly cause many severe health problems. Although the toxicity of nanoparticles has been investigated, prevention and treatment of damages caused by nanoparticles have been rarely studied. Therefore, isotope tracing and improved CT imaging techniques were used to investigate the biodistribution influence between oMWCNTs(oxidized multi-walled carbon nanotubes) and 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC)/or simvastatin (TD) in vivo. What’s more, biochemical indices in plasma and tissue histology were measured to further study therapeutic effects on the damages of oMWCNTs in mice. Isotope tracing and improved CT imaging results showed that low dosages of DOPC and TD didn’t affect the distribution of oMWCNTs in mice; conversely, the distribution and metabolism of DOPC and TD were influenced by oMWCNTs. Moreover, DOPC and/or TD improved the biocompatibility of oMWCNTs in erythrocyte suspension in vitro. Biochemical index and histopathological results indicated that DOPC and TD didn’t prevent injuries caused by oMWCNTs effectively. But TD showed a good therapeutic effect for damages. This study is the first to investigate prevention and treatment effects of drugs on damages caused by oMWCNTs and provides new insights and breakthroughs for management of nanoparticles on health hazards.